Solid fuel use in rural China and its health effects. (July 2016) - Liao, Hua; Tang, Xin; Wei, Yi-Ming
Abstract: Solid fuels such as firewood and coal are widely used for cooking and heating in the developing countries, which result in serious indoor air pollutions and health effects. Governments and international organizations have been devoted to addressing this issue for a long time. Based on the micro survey data from 1989–2011, this paper quantitatively investigate the situations and evolutions of cooking fuel using and its health effects in rural China. We have four findings: (i) most rural households still rely on solid fuels for cooking in modern China. (ii) the cooking fuels are slowly diversifying in the last two decades, (iii) there are considerably geographical differences in cooking fuel using across China, and (iv) those resident usually using solid fuel have lower levels of self-assessed health and higher prevalence of respiratory diseases. We then draw some policy implications to reduce cooking fuel use.